THE WORD SORT STRATEGY TO IMPROVE STUDENT’S ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Ratna Soraya; Nana Mardiana; Rika Kartika; Rizka Elfira (Ensiklopedia of Journal, 2022)
This study attempted to improve students’ writing achievement through The Word Sort Strategy. This study was conducted by using classroom action research. The subject was class X in SMA Amir Hamzah Medan that consisted of 40 students. The study was conducted in two cycles; cycle I consisted of three meetings (meeting I, II, and III) and cycle II consisted of three meetings (meeting IV, V, and VI). The instruments for collecting data were quantitative data (writing test) and qualitative data (interview sheet, observation sheet and diary notes). Based on writing tests’ scores, the mean of the students’ scores in the second cycle was 79.35 and in the first cycle as 71.95. Based on the interview sheet, observation sheet and diary notes, it was found that students interested in applying Word Sort Strategy because it helped them to improve their writing achievement. The result showed that Word Sort Strategy can improve students’ writing achievement.